2013
DOI: 10.4103/2141-9248.122109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of helicobacter pylori infection among patients undergoing upper gastrointestinal endoscopy in a medical college hospital in Kerala, India

Abstract: Background:Helicobacter pylori related gastritis is a major health ailment in developing nations. There is high morbidity and mortality ranging from chronic gastritis to gastric malignancies. Prevalence of H. pylori infection varies markedly from country to country and in a country, region to region.Aim:To study the prevalence of H. pylori gastritis in patients undergoing endoscopy and its association with the development of gastrointestinal diseases.Subjects and Methods:The study was carried out in a Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 15 publications
9
37
1
2
Order By: Relevance
“…In Asia, the studies published over the last year showed high prevalence rates of H. pylori infection ranging from 54% to 76% [10][11][12][13][14][15][16]. Only one study carried out on healthy individuals in Saudi Arabia showed a low prevalence of infection of about 28% [17].…”
Section: Prevalence Of Helicobacter Pylori Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, the studies published over the last year showed high prevalence rates of H. pylori infection ranging from 54% to 76% [10][11][12][13][14][15][16]. Only one study carried out on healthy individuals in Saudi Arabia showed a low prevalence of infection of about 28% [17].…”
Section: Prevalence Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Gender and age do not seem to be associated with an increased risk of infection. Indeed, most studies reported no significant difference of H. pylori infection between men and women, both in adults [3,13,[15][16][17]20,21] and in children [23,24,27]. No significant association was found between infection and age in the adult population [4,8,13,14,16,17,23].…”
Section: Risk Factors For Helicobacter Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In our study, the presence of H. pylori was 35%; with prevalence being more among alcoholics. The low incidence in our study could be due to the use of only a single method (RUT) to detect H. pylori.…”
Section: Discussionmentioning
confidence: 82%
“…11 The prevalence of H pylori in gastric biopsy is 58.7 % similar to other studies in South India, showing 59.4 % prevalence. 12 According to this study, the sensitivity and specificity of H&E stain were 75.86%, and 98.41%, respectively. This is in concordance with similar studies showing sensitivity of 70% -98 % and specificity of 90-98% with H&E stain .However in cases showing low density of organisms, the specificity of H&E was low compared to Giemsa.…”
Section: Resultsmentioning
confidence: 99%